2001
DOI: 10.1016/s1074-7613(01)00254-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of E2F2 in Mice Causes Enhanced T Lymphocyte Proliferation, Leading to the Development of Autoimmunity

Abstract: E2Fs are important regulators of proliferation, differentiation, and apoptosis. Here we characterize the phenotype of mice deficient in E2F2. We show that E2F2 is required for immunologic self-tolerance. E2F2(-/-) mice develop late-onset autoimmune features, characterized by widespread inflammatory infiltrates, glomerular immunocomplex deposition, and anti-nuclear antibodies. E2F2-deficient T lymphocytes exhibit enhanced TCR-stimulated proliferation and a lower activation threshold, leading to the accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
160
3
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(172 citation statements)
references
References 44 publications
(2 reference statements)
8
160
3
1
Order By: Relevance
“…These results argue for a positive role for E2F1-3 in cell cycle progression. By contrast, we and others have shown that loss of E2F2, or more dramatically, the combined loss of E2F1 and E2F2 impairs cellular quiescence and leads to accelerated replication of DNA of several cell types, implying a negative role for these proteins in proliferation control (Murga et al, 2001;Zhu et al, 2001;Infante et al, 2008;Pusapati et al, 2010). Moreover, loss of E2F leads to deficient erythropoiesis, which has been associated with increased DNA double-stranded breaks and cell cycle arrest (Dirlam et al, 2007), although the source of the DNA damage has not been identified.…”
Section: Introductioncontrasting
confidence: 66%
See 3 more Smart Citations
“…These results argue for a positive role for E2F1-3 in cell cycle progression. By contrast, we and others have shown that loss of E2F2, or more dramatically, the combined loss of E2F1 and E2F2 impairs cellular quiescence and leads to accelerated replication of DNA of several cell types, implying a negative role for these proteins in proliferation control (Murga et al, 2001;Zhu et al, 2001;Infante et al, 2008;Pusapati et al, 2010). Moreover, loss of E2F leads to deficient erythropoiesis, which has been associated with increased DNA double-stranded breaks and cell cycle arrest (Dirlam et al, 2007), although the source of the DNA damage has not been identified.…”
Section: Introductioncontrasting
confidence: 66%
“…In line with the original model of E2F function, overexpression of E2F1 in immortalized quiescent rodent fibroblasts results in increased DNA replication and cell proliferation (Lukas et al, 1996), and overexpression of E2F2 in thymic epithelial cells results in the development of thymomas (Scheijen et al, 2004). Furthermore, knockout of E2F1 in mouse embryo fibroblasts or in T lymphocytes modestly slows progression from quiescence to S phase (Wang et al, 1998;Murga et al, 2001), and E2F2 À/À and E2F1/E2F2 À/À mice exhibit impaired hematopoiesis resulting from defective S-phase progression in progenitor populations (Li et al, 2003). The combined inactivation of E2F1, 2 and 3 completely abolishes entry into S phase and proliferation, along with reduced expression of E2F target genes necessary for these processes (Wu et al, 2001).…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Colonies of E2F1 − / − , E2F2 − / − and DKO E2F1 − / − /E2F2 − / − mice have been described. 19,51,52 p53 − / − and p21 CIP1 − / − mice have also been described. 25,53 DKO E2F1 − / − /E2F2 − / − mice were bred to p53 − / − or p21 CIP1 − / − mice to generate TKO E2F1 − / − /E2F2 − / − /p53 − / − or E2F1 − / − /E2F2 − / − /p21 CIP1 − / − animals.…”
Section: Methodsunclassified